2009
DOI: 10.1099/vir.0.004416-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of indoleamine 2,3-dioxygenase in serum from acutely infected dengue patients linked to gamma interferon antiviral function

Abstract: The depletion of L-tryptophan (L-Trp) has been associated with the inhibition of growth of microorganisms and also has profound effects on T cell proliferation and immune tolerance. The enzyme indoleamine 2,3-dioxygenase (IDO) catalyses the rate-limiting step in the catabolic pathway of LTrp. Gene expression analysis has shown upregulation of genes involved in L-Trp catabolism in in vitro models of dengue virus (DENV) infection. To understand the role of IDO during DENV infection, we measured IDO activity in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 31 publications
1
30
0
8
Order By: Relevance
“…Thus, IDO1 is up-regulated in vivo following infection with HSV-1 (herpes simplex virus type 1) [531], poliovirus (which causes poliomyelitis) [532], hepatitis C [533,534], dengue virus [535], Epstein-Barr virus (which causes glandular fever) [536], encephalomyocarditis virus (which causes encephalitis and myocarditis primarily in pigs) [537,538], LP-BM5 murine leukaemia virus (murine AIDS) [502], SIV (simian immunodeficiency virus) [539] and HIV [540][541][542][543].…”
Section: Expression Of Ido1 In Vitro and In Vivo In Response To Viralmentioning
confidence: 99%
“…Thus, IDO1 is up-regulated in vivo following infection with HSV-1 (herpes simplex virus type 1) [531], poliovirus (which causes poliomyelitis) [532], hepatitis C [533,534], dengue virus [535], Epstein-Barr virus (which causes glandular fever) [536], encephalomyocarditis virus (which causes encephalitis and myocarditis primarily in pigs) [537,538], LP-BM5 murine leukaemia virus (murine AIDS) [502], SIV (simian immunodeficiency virus) [539] and HIV [540][541][542][543].…”
Section: Expression Of Ido1 In Vitro and In Vivo In Response To Viralmentioning
confidence: 99%
“…Unfortunately, sera IDO activity has only rarely been investigated in infectious diseases. In this connection, Becerra et al [47] found increased IDO activity in the sera of dengue virus (DENV)-infected patients during the most febrile days of the disease, indicating that IDO activity was at least partially dependent upon IFN-g.…”
Section: Hla-drmentioning
confidence: 99%
“…Infection with dengue virus, HIV, poliovirus, and hepatitis C virus is associated with IDO induction in various tissues and cell types, both in vivo and in vitro (19)(20)(21)(22). Previously reported evidence suggests that EBV infection increases the expression level of IDO in B cells and inhibits NK cell cytotoxicity (23).…”
mentioning
confidence: 99%